German stagnation vs. Swedish progression: Gender wage gaps in comparison, 1960-2006 - Svenja Gärtner (Luxembourg Income Study (LIS), 2013)
This article provides a comparative analysis of the development of the gender wage gap in West Germany and Sweden during the period 1960-2006. Despite the economic similarities including broad social safety nets, the gap has developed differently since 1960. This analysis accounts for micro- and macroeconomic factors and politics and concludes that norms and traditions penetrate institutional settings and ensnare Germany in a cultural trap with regard to gender equality. While Sweden has moved to a two-earner model, German society expects mothers to stay at home. The micro analysis shows that family concerns (e.g., marriage and motherhood) decrease female income in Germany to a far greater extent than do such factors in Sweden, which can be explained in part by deeply held social attitudes.
Keywords: N34; J16; I38; J31; Z1; 330; culture; gender wage gap; Germany; Sweden; welfare state; Lohnstruktur; Mikrodaten; Deutschland; Schweden